Empirical Investigation of factors affecting information and communication technologies (icts) in Agric-Business among small scale farmers in Esan Community, Edo State, Nigeria - Awojide, Simon; Akintelu, Sunday Olufemi (Journal of Research in Marketing (ISSN: 2292-9355), 2018)
ICTs are vital technologies for the development of agricultural sector in Nigeria. Its usage has created wealth to many, both in developed and developing countries. The study evaluated the usage of ICT in agricultural practices and determined factors influencing its usage among farmers in Esan community of Edo State, Nigeria. Data used for the study were generated from a sample of 75 respondents using structured questionnaire and interview schedule. Data collected were analysed using inferential statistical method. The result of ANOVA analysis revealed that factors limiting the use of ICT on farming activities among small scale farmers in the community include inability of farmers to use ICT (0.017 ≤ 0.05), lack of technological infrastructure (0.012 ≤ 0.05), cost of technology (0.039 ≤ 0.05), fear of technology (0.015 ≤ 0.05), time to spend on technology (0.026 ≤ 0.05), value of ICT (0.011 ≤ 0.05) and trustworthiness (0.007 ≤ 0.05). These factors are significant at 0.05 level of significance and tend to have varying impact on the adoption of ICT with respect to age, implying that lower age group tend to favour factors such as: time spent on technology, value of ICT and trustworthiness, while higher age group are compatible with technological infrastructure and the inability to use ICT. The study concluded that the adoption of ICT begins at lower age group, While, at higher age group, this tendency tends to decline. The study recommends that aggressive policy of digital revolution should be lunch in the community and could re-orient farmers and make them conversant with the beneficial effect of ICT in agricultural process.